Literature Review: Analysis of Potential Human Error Factors in the Industrial Sector Using the Heart Method - Hasanuddin Hasanuddin; Husaini Husaini; Erida Wydiamala; Lenie Marlinae; Silvia Kristanti Tri Febriana (GLOBAL HEALTH SCIENCE GROUP, 2026)
Occupational Health and Safety (OHS) is a fundamental aspect of the industrial world, playing a crucial role in protecting workers and ensuring operational continuity. Various reports indicate that the majority of workplace accidents in industrial sectors, such as mining, construction, and manufacturing, are still dominated by human error. Therefore, a comprehensive evaluation of the probability of human error is necessary to reduce the number of workplace accidents and improve safety performance. Objective to analyze and integrate research findings related to the implementation of the Systematic Human Error Reduction and Prediction Approach (SHERPA) and Human Error Assessment and Reduction Technique (HEART) methods in identifying, measuring, and reducing the risk of human error in various industrial sectors. This study is a systematic literature review compiled according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Articles were searched through Google Scholar and PubMed databases using the keywords